SISTEM PELAYANAN ADMINISTRASI PEMBUATAN AKTA KELAHIRAN MASYARAKAT DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN PADANG PARIAMAN - Puryanto Puryanto; Andika Putra (Ensiklopedia of Journal, 2021)
The administrative service system at the Department of Population and Civil Registration of Padang Pariaman Regency, especially in managing birth certificates, still occurs problems related to the administrative service system provided. People want an excellent service or also called Excellent service. And currently, services that need to be improved include the processing of birth certificate documents at the Department of Population and Civil Registration of Padang Pariaman Regency. In the future, in serving the need for innovation in improving the services provided. Because currently there are still people who often complain that the time for completion of services is delayed and does not comply with the set schedule. The research objective was to determine the administrative service system for making birth certificates. This study used a qualitative descriptive method, while the data collection technique was carried out through in-depth interviews with selected key informants and direct observation of the object and subject of the study. Based on the results of the research conducted, the administrative service system for making birth certificates can be seen from several indicators, namely: Ability, attitude, appearance, attention, action, and responsibility. The results of this study indicate that the administrative service system for making birth certificates is still lacking in services provided and inaccurate service time for making birth certificates, obstacles encountered in the Department of Population and Civil Registration of Padang Pariaman Regency, there are still many people who do not know the process of making a birth certificate. In the future, the Department of Population and Civil Registration of Kabupaten Padang Pariaman provides socialization and education during the implementation of the administrative service process for making birth certificates to the public. In conclusion, the administrative service system for making birth certificates at the Department of Population and Civil Registration of Kabupaten Padang Pariaman must make new innovations in improving future services.